FAKTOR PENYEBAB FASAKH DI DESA SEKURA KECAMATAN TELUK KERAMAT KABUPATEN SAMBAS PADA TAHUN 2022 - Sharmila, Lela; Sartika, Enik; Lamazi, Lamazi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
Marriage is a natural aspect of human life, with the primary goal of forming a harmonious and loving family. For Muslims, marriage is not only influenced by local customs but is also considered an act of worship. While it is hoped to bring happiness, marital life often faces various challenges that, if unresolved, can lead to fasakh (annulment). This study aims to describe the causes of fasakh in Desa Sekura. The research focuses on the factors causing fasakh and the specific issues related to it in Desa Sekura, Kecamatan Teluk Keramat. The methodology used in this research is qualitative, with a case study approach. Data were collected through observation, interviews, and documentation, and then analyzed through data reduction and verification. The results indicate that fasakh among married couples in Desa Sekura, Kecamatan Teluk Keramat, is primarily caused by economic factors, such as insufficient financial support from the husband. Additionally, infidelity and various forms of abuse, both physical and verbal accusations made by the husband towards the wife, also significantly influence the decision of couples to pursue fasakh. The type of fasakh occurring in Desa Sekura is indirect, involving the intervention of a judge at the Religious Court of Kabupaten Sambas, following several stages of hearings before the judge's decision is made.